2021
DOI: 10.1108/nfs-11-2020-0421
|View full text |Cite
|
Sign up to set email alerts
|

Do body mass index (BMI) and history of nutritional supplementation play a role in the severity of COVID-19? A retrospective study

Abstract: Purpose The coronavirus disease 2019 (COVID-19) is an infectious disease that puts strain on health-care systems. Obesity is considered as a risk factor for the severity of infection. Hypotheses also suggested some nutritional supplements may be useful in COVID-19. This paper aims to assess the role of body mass index (BMI) and nutritional supplements on the severity of COVID-19. Design/methodology/approach This research was conducted on 603 participants (in five groups including: exposure to virus and healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The severity of clinical symptoms in positive COVID-19 patients is varied, ranging from asymptomatic to acute respiratory distress syndrome and multi-organ dysfunction [6]. Previous researches reported male sex, older age, and chronic diseases such as diabetes, hypertension, and obesity as the risk factors for severe clinical symptoms of COVID-19 [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The severity of clinical symptoms in positive COVID-19 patients is varied, ranging from asymptomatic to acute respiratory distress syndrome and multi-organ dysfunction [6]. Previous researches reported male sex, older age, and chronic diseases such as diabetes, hypertension, and obesity as the risk factors for severe clinical symptoms of COVID-19 [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that taking vitamin supplements in the past six months, did not affect the severity of clinical symptoms in people who have experienced COVID-19 (Mohseni et al , 2021). Additionally, a number of review studies and commentary have suggested that nutrients can strengthen the immune system, which may contribute to the prevention of COVID19 (Calder et al , 2020; Muscogiuri et al , 2020; Calder, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Many surveys recommend nutritional supplements for improving immunity against coronavirus infection. Mohseni et al compared the COVID-19 infected patients for the induced immunity following nutritional consumption; their findings revealed that the higher BMI as a risk factor was not influenced, and patients with higher BMI had a higher severity of infection (15).…”
Section: Discussionmentioning
confidence: 99%